CONGRATULATIONS" AS A MANIFESTATION OF FOLK CULTURE - Yuldasheva Sabina Yusufovna (Web of Journals Publishing, 2025)
This article examines "congratulations" as a phenomenon of folk culture.
Keywords: Natural written Russian speech (NWRS), genre